Monolithic Fabrication of Metal-Free On-Paper Self-Charging Power Systems - Su, Yingchun; Xue, Han; Fu, Yujie; Chen, Shiqian; Li, Zheng; Li, Lengwan; Knoks, Ainars; Bogdanova, Olga; Lesničenoks, Pēteris; Palmbahs, Roberts; Laurila, Mika-Matti; Mäntysalo, Matti; et al. (Wiley, 2024)
Self-charging power systems (SCPSs) are envisioned as promising solutions for emerging electronics to mitigate the increasing global concern about battery waste. However, present SCPSs suffer from large form factors, unscalable fabrication, and material complexity. Herein, a type of highly stable, eco-friendly conductive inks based on poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) are developed for direct ink writing of multiple components in the SCPSs, including electrodes for miniaturized spacer-free triboelectric nanogenerators (TENGs) and microsupercapacitors (MSCs), and interconnects. The principle of “one ink, multiple functions” enables to almost fully print the entire SCPSs on the same paper substrate in a monolithic manner without post-integration. The monolithic fabrication significantly improves the upscaling capability for manufacturing and reduces the form factor of the entire SCPSs (a small footprint area of ≈2 cm × 3 cm and thickness of ≈1 mm). After pressing/releasing the TENGs for ≈79000 cycles, the 3-cell series-connected MSC array can be charged to 1.6 V while the 6-cell array to 3.0 V. On-paper SCPSs are promising to serve as lightweight, thin, sustainable, and low-cost power supplies. © 2024 The Authors. Advanced Functional Materials published by Wiley-VCH GmbH. --//-- This is an open-access article Y. Su, H. Xue, Y. Fu, S. Chen, Z. Li, L. Li, A. Knoks, O. Bogdanova, P. Lesničenoks, R. Palmbahs, M.-M. Laurila, M. Mäntysalo, M. Hammar, A. Hallén, N. Nordell, J. Li, Monolithic Fabrication of Metal-Free On-Paper Self-Charging Power Systems, Adv. Funct. Mater. 2024, 34, 2313506. https://doi.org/10.1002/adfm.202313506 published under the CC BY-NC-ND licence.
The authors acknowledge the financial support from the Swedish Research Council (Grant No. 2019-04731) and the European Commission (Grant No. 101070255, REFORM). The authors also acknowledge the mobility support from the the European Union’s Horizon 2020 Framework Program H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2, and the Swedish Foundation for International Cooperation in Research and Higher Education (STINT, CH2017-7284).
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; direct ink writing; microsupercapacitors; paper electronics; self-charging power systems; triboelectric energy harvesters